1997
DOI: 10.1128/jcm.35.12.3098-3103.1997
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus and host variables as predictors of clinical course in patients with juvenile-onset recurrent respiratory papillomatosis

Abstract: This study provides the first systematic evaluation of papillomavirus type and viral mutation occurring during the course of juvenile-onset recurrent respiratory papillomatosis. One hundred ninety-nine consecutive papillomas excised from 47 children between 1981 and 1996 at The New Children's Hospital in Sydney, Australia, were tested for human papillomavirus (HPV) DNA by PCR. PCR products from the viral upstream regulatory region (URR) enhancer were sequenced, and variation was related to clinical variables. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 30 publications
2
58
0
1
Order By: Relevance
“…Severe forms of recurrent respiratory papillomatosis were defined as any of the following: Derkay anatomical score ≥10, more than 10 surgeries overall or any tracheal involvement. This definition was selected to incorporate both the objective Derkay anatomical scale and the number of surgical procedures mostly used in the literature [Gabbott et al, ; Rabah et al, ; Draganov et al, ; Buchinsky et al, ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Severe forms of recurrent respiratory papillomatosis were defined as any of the following: Derkay anatomical score ≥10, more than 10 surgeries overall or any tracheal involvement. This definition was selected to incorporate both the objective Derkay anatomical scale and the number of surgical procedures mostly used in the literature [Gabbott et al, ; Rabah et al, ; Draganov et al, ; Buchinsky et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…There is a paucity of good quality data on risk factors associated with disease severity [Pou et al, ; Gabbott et al, ; Rimell et al, ; Armstrong et al, ; Rabah et al, ; Reeves et al, ; Bonagura et al, ; Wiatrak et al, ; Gerein et al, ; Draganov et al, ; Maloney et al, ; Leung et al, ; Buchinsky et al, ; Bonagura et al, ; Carvalho et al, ]. In most of the studies, HPV11 was associated with a worse prognosis [Rimell et al, ; Rabah et al, ; Gerein et al, ; Draganov et al, ; Maloney et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subtypes of HPV-6 were distinguished by restriction endonuclease digestion patterns, which may identify viral types less accurately than polymerase chain reaction (PCR). Gabbott et al 96 demonstrated no significant difference in disease severity in a population of 47 children with RRP over a 15-year period, with an equal distribution of HPV-6 (55%) and HPV-11 (43%). Padayachee and Prescott 97 reported more severe disease in children with HPV-6 versus HPV-11.…”
Section: Risk Factors For Aggressive Diseasementioning
confidence: 97%
“…HPV types 6 and 11 account for most cases of RRP. HPV-11 occurs most commonly (50%-100% of isolates) [9][10][11][12][13][14] and runs the most aggressive clinical course, followed by HPV-6. HPV types 16, 18, 31, and 33 have also been reported in RRP, albeit rarely.…”
Section: Causes/epidemiology Of Rrpmentioning
confidence: 99%